PENGARUH MEDIA BUKU CERITA BERGAMBAR TERHADAP PENGETAHUAN TENTANG MANAJEMEN BENCANA KABUT ASAP PADA ANAK USIA 4-5 TAHUN DI TK ISLAM AL AZHAR 54 KECAMATAN TAMPAN KOTA PEKANBARU - Nurul Aini; Yeni Solfiah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on observations in the field it can be seen that the knowledge of haze disaster management in children aged 4-5 years is still in the sufficient category, so it is necessary to use the picture book media. This study aims to determine the effect of illustrated storybook media on knowledge about haze disaster management. This research was conducted in Islam Al Azhar Kindergarten 54 Pekanbaru City. This study used an experimental method with one group pretest posttest design with a sample of 15 children and used a saturated sample technique. Data collection techniques in this study were observation techniques. The data analysis technique used the t-test using the SPSS 21 program. The results of the data analysis can be obtained t count 20.589 is greater than t table 2.145 with a significance of 0.000 <0.05. It can be concluded that there are differences in knowledge about haze disaster management before and after the use of picture story book media. The influence given by the media illustrated story books based on the N Gain formula of 70.87% was in the high category. Key Words:  The Media Of Picture Books, Smog Disaster Management